The Role of Intellectual Capital to Fill the Missing Link in The Relationship Between Social Responsibility and Islamic Banking Performance in Indonesia - Pratama, Bima Cinintya; Makhrus, Makhrus; Innayah, Maulida Nurul (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
The purpose of this research is to analyse how Islamic banks in Indonesia performance using antecedents of their level of social responsibility and intellectual capital. In addition, the mediating role of IC in the connection between CSR and firm performance is examined. This study predicts that CSR strategies have the potential to enhance corporate IC, giving rise to a new type of IC called "Sustainable IC," which is closely related to environmental and social knowledge that businesses must have in order to thrive in the modern business world. This study result’s confirmed the mediating role of IC in the connection between CSR and performance. This study's findings have important practical implications for banks, which may use them to justify spending more on CSR implementation techniques that boost CSR indicators linked to more extensive use of IC resources and, hence, improved business outcomes. The findings also support the positive impact of IC and social responsibility on the performance of Islamic banks in Indonesia, demonstrating the existence of a causal link between the two